Astragalus mongholicus powder, a traditional Chinese medicine formula ameliorate type 2 diabetes by regulating adipoinsular axis in diabetic mice - Xu, Siyuan; Ye, Bixian; Li, Jinlei; Dou, Yonghui; Yu, Yuying; Feng, Yifan; Wang, Lexun; Wan, David Chi-Cheong; Rong, Xianglu (Frontiers in Pharmacology, 2022)
The global morbidity of obesity and type 2 diabetes mellitus (T2DM) has dramatically increased. Insulin resistance is the most important pathogenesis and therapeutic target of T2DM. The traditional Chinese medicine formula Astragalus membranaceus powder (APF) has long been used to treat “Xiaoke”, former name of diabetes in ancient China, and consists of Astragalus membranaceus, Pueraria lobata, and root bark of Morus alba L. This work aims to validate the effects of APF on diabetic mice and investigate the underlying mechanism. Classic high-fat-diet (HFD) and streptozotocin (STZ)-induced type 2 diabetic animal mouse models were established. The body weight of mice and their plasma levels of glucose, insulin, leptin and lipids were estimated. Reverse transcription-polymerase chain reaction, histology, and Western blot analysis were performed to validate the effects of APF on diabetic mice and investigate the underlying mechanism. APF could reverse hyperglycemia, hyperinsulinemia, and hyerleptinemia and attenuate obesity and non-alcoholic fatty liver disease (NAFLD) development. However, these effects could not observe in leptin deficient ob/ob diabetic mice and STZ-induced insulin deficient type 1 diabetic mice. Destruction of either these hormones would abolish the therapeutic effects of APF. In addition, APF inhibited the protein expression of PTP1B suppressing insulin–leptin sensitivity, the gluconeogenic gene PEPCK, and the adipogenic gene FAS. Therefore, insulin–leptin sensitivity was normalized, and the gluconeogenic and adipogenic genes were suppressed. In conclusion, APF regulated the balance of adipoinsular axis and alleviated obesity, NAFLD and T2DM in STZ+HFD induced T2DM mice because of its suppressive effects on PTP1B expression.